Evaluation of erosion models and field assessment methods as tools for monitoring and evaluation of soil erosion in landcare - Claassens, A.S. (Andries Stephanus), 1943- (University of Pretoria, 2013)
Dissertation (MSc (Agriculture))--University of Pretoria, 2006.